CSF tau phosphorylation at sites 217 and 181 are associated with preclinical and biphasic alterations in resting‐state functional connectivity in Autosomal Dominant AD. (20th December 2022) - Meeker, Karin L.; Barthélemy, Nicolas R.; Gordon, Brian A.; McDade, Eric; Karch, Celeste M.; Fagan, Anne M.; Strain, Jeremy F.; Luckett, Patrick H; Benzinger, Tammie L.S.; Bateman, Randall J.; Holtzman, David M.; Ances, Beau M; et al.
Abstract: Background: In autosomal dominant AD (ADAD), elevated cerebrospinal fluid (CSF) soluble phosphorylated tau (pT181) increases shortly after amyloid positron emission tomography. Recent advancements have identified additional phosphorylated tau sites, such as phosphorylated tau 217 and 205 (pT217 and pT205), which are associated with amyloid deposition and neuronal dysfunction, respectively. Degradation of cortical brain network resting‐state functional connectivity (RS‐FC) is typically observed at the onset of cognitive impairment and is most prevalent in regions where amyloid and tau accumulate. However, it is unknown how specific phosphorylated tau sites are associated with alterations in brain networks and contribute to the transition from asymptomatic to symptomatic AD. Method: CSF tau phosphorylation occupancy on 217, 181 and 205 residues and RS‐FC were measured in 93 individuals from the Dominantly Inherited Alzheimer Network (amyloid‐negative asymptomatic mutation carrier [(aMCA‐); n=26]; amyloid‐positive asymptomatic mutation carriers [a(MCA+); n=36]; and amyloid‐positive symptomatic mutation carriers [(sMCA+); n=31]). Regression models were used to determine within‐group associations between CSF phosphorylated tau sites and within‐network RS‐FC measures. Result: P‐tau associated RS‐FC alterations began during preclinical stages and continuously changed throughout disease progression. Specifically, within aMCA‐, pT217, pT181, and pT205 were associated with decreased RS‐FC in salience and ventral attention networks, while in aMCA+, pT217 and pT181 were associated with increased RS‐FC in the fronto‐parietal network. In sMCSA+ elevated p‐tau sites were associated with decreased RS‐FC in the cingulo‐opercular, dorsal attention, default mode, and memory networks. Conclusion: Elevated phosphorylation at specific tau sites is associated with a biphasic pattern of RS‐FC which begins during asymptomatic stages. P‐tau‐ associated RS‐FC alterations were consistent with proposed models of cascading network failure and AD pathophysiology. These results suggest that in ADAD, phosphorylation of tau is associated with widespread and dynamic RS‐FC alterations which begin before the transition to symptomatic AD.